A comprehensive description of the 1 August 2021 Azzano Decimo hailstorm in northeastern Italy - Manzato, Agostino; Knight, Charles; Kumjian, Matthew R.; Stenni, Barbara; Dreossi, Giuliano; Masiol, Mauro; Zhang, Qinghong; Lin, Xiangyu; Heymsfield, Andrew (Frontiers in Environmental Science, 2026)
On 1 August 2021, a vigorous hailstorm hit Azzano Decimo, in northeastern Italy. The supercell storm produced hailstones up to 10 cm in maximum dimension, which is quite unusual in this area. The storm’s environment registered one of the largest potential instabilities (>3400 J kg−1) ever observed by the local operational Udine radiosonde site. In this paper, we analyze the mesoscale environment supporting the hailstorm. Observations from the nearby operational Fossalon di Grado dual-polarization radar showed the presence of a pronounced Bounded Weak Echo Region and differential reflectivity column, both proxies for intense updrafts; however, Doppler velocities revealed only weaker winds, with the mesocyclone mostly confined to midlevels. Two independent observers in Azzano Decimo collected nine hailstones, including one with a maximum dimension of 9 cm. The physical structure of these hailstones was analyzed in the National Center for Atmospheric Research cold room, including normal and cross-polarized light photographs of thin sections to identify the different growth layers inside each hailstone. Additionally, ice samples were taken from 1 cm ×1 cm ×1 mm pieces from these thin slices. The stable isotopic ratio analyses were performed on these specimens using a Picarro cavity ring-down spectrometer. Isotopic content of the hailstone layers revealed significant variability, including some internal layers that showed signs of kinetic fractionation owing to evaporating liquid being incorporated into the growth layer, likely from evaporation of surface liquid during wet growth or collection of recirculated raindrops that experienced evaporation prior to participating in hail growth. Despite such large isotope variability, the Jouzel model analysis suggested that the major growth happened at high altitudes (between 8 and 10 km), which is also in agreement with a reversible-adiabatic parcel model and radar observations from the event.